1996
DOI: 10.1148/radiology.199.3.8637982
|View full text |Cite
|
Sign up to set email alerts
|

Detection and treatment of dysfunctional hemodialysis access grafts: effect of a surveillance program on graft patency and the incidence of thrombosis.

Abstract: The hemodialysis graft surveillance program resulted in a statistically significant reduction in the incidence of graft thrombosis. Although primary patency rates after PTA were low, repeated PTA of detected stenoses allowed good primary assisted patency rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
103
0
4

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(113 citation statements)
references
References 0 publications
6
103
0
4
Order By: Relevance
“…A number of studies have evaluated the positive predictive value of an abnormality of clinical AVG monitoring or surveillance for the presence of hemodynamically significant stenosis. The values were 69%-93% for clinical monitoring (80% for physical examination, 69% for unexplained decrease in Kt/V, and 66% for difficulties encountered during the dialysis session) (3,5,(8)(9)(10), 92% for static dialysis venous pressure (6), 87%-100% for flow monitoring (11,12), and 80% for duplex ultrasound (5).…”
Section: Can One Identify Avgs With Significant Stenosis By Noninvasimentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have evaluated the positive predictive value of an abnormality of clinical AVG monitoring or surveillance for the presence of hemodynamically significant stenosis. The values were 69%-93% for clinical monitoring (80% for physical examination, 69% for unexplained decrease in Kt/V, and 66% for difficulties encountered during the dialysis session) (3,5,(8)(9)(10), 92% for static dialysis venous pressure (6), 87%-100% for flow monitoring (11,12), and 80% for duplex ultrasound (5).…”
Section: Can One Identify Avgs With Significant Stenosis By Noninvasimentioning
confidence: 99%
“…Such an approach makes sense intuitively. In fact, numerous observational studies have reported that implementation of routine AVG stenosis surveillance, in conjunction with preemptive angioplasty, markedly lowers the frequency of AVG thrombosis in comparison with a historical period without AVG surveillance (6,9,10,(15)(16)(17). More recently, six randomized clinical trials (RCTs) have evaluated this research question (4,5,12,(18)(19)(20) (Figure 2).…”
Section: Does Stenosis Surveillance With Preemptive Angioplasty Prevementioning
confidence: 99%
“…Stenosis of the arterial inflow can also be effectively treated via PTA [21]. Several workgroups even observed success rates of 98 % [78]. PTA can be performed without complication if only the afferent artery proximal to the vascular access or the anastomosis is affected but the artery distal to the anastomosis is not stenosed.…”
Section: Insufficient Dialysis Graftmentioning
confidence: 99%
“…Patients were referred to interventional radiology for a fistulogram when any of the following abnormalities was noted: (1) persistent elevation of dialysis venous pressures (DVP) at a low blood flow during initiation of dialysis, (2) prolonged bleeding from needle puncture sites in the graft, (3) unexplained progressive decrease in Kt/V, or (4) abnormal graft inspection and auscultation (18). We have previously reported that aggressive clinical monitoring of grafts and referral for a fistulogram when any one of these abnormalities was detected decreased the frequency of graft thrombosis by 60% (13).…”
Section: Management Of Dialysis Grafts and Their Complicationsmentioning
confidence: 99%